Screening of the homopolymerization and copolymerization of vinylmelamines. (June 2016) - Heschik, Michael; List, Manuela; Schwarzinger, Clemens
Graphical abstract: Highlights: Homo- and copolymerizations of vinylated melamine derivatives are possible. Crosslinked and linear systems accessible. Copolymerizations with acrylates favoured compared to styrene. Improved thermal properties by incorporation of vinyl melamines into acrylate and styrene copolymers. Abstract: The free radical polymerization characteristics of various vinylated melamine derivatives, cross linking and linear, were analysed by GC/MS and HPLC/PDA measurements. Special attention was put on the general progress of the polymerization as well as on the opportunity for copolymerizations with common monomers like methyl methacrylate and styrene. In order to retrieve thermal properties of the (co)polymers also larger scale polymerizations have been done, showing that thermal stability can be increased by incorporation of vinylmelamines. Also the glass transition temperature can be increased linearly by increasing amounts of vinyl pentamethylmelamine in styrene and methyl methacrylate copolymers.